Antioxidant and anticancer properties of crude extracts from dedalu (Helixanthera parasitica lour.) - Duraivelu, Thirubuvanesvari (2019)
Loranthaceae is a mystique plant that has been utilized ethnobotanically as medicinal plant in Southeast Asia countries. Up to now and to the best of our knowledge very scarce research has been conducted on this species to exploit its further medicinal potential particularly on exploring its antioxidant capacity and towards one of the leading non-communicable disease (NCD), that has remained difficult to treat but preventable, the breast cancer. The present study was designed to prepare different extracts from the leaves and stem of H. parasitica and to determine their total phenol, flavonoids content, antioxidant activity as well as selecting the best extracts towards anticancer assay by applying established methods. Different extracts were prepared by maceration technique with powdered leaves and stem sample. Extraction of both plant part were performed separately using solvents of different polarity, namely, distilled water (dH2O), methanol (70% and 100), acetone (70% and 100%) and petroleum ether. The parameters targeted on the plant extracts were determined using Total Phenolic Content (TPC)/ Folin-Ciocalteu reagent (FCR), Total Flavonoid Content (TFC)/ aluminium chloride (AlCl3), 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) and MTT (for anticancer assay) method. Highest extract yield was obtained from leaf extracts (679.13 ± 9.60 mg/g DW) and the yields of extraction by various solvents decreased in the following order: 70% acetone > 70% methanol > 100% methanol > 100% acetone > dH2O > petroleum ether. Leaf extract from pure acetone solvent was found to exhibit highest TPC (99.45 ± 12.87 mg GAE/g DW), TFC (17.57 ± 0.63 mg QE/g DW) and DPPH (81.61 ± 1.22 %) with no significant difference found between leaf and stem evaluated from TPC and DPPH. This extract also showed slightly lower FRAP value (6.73 ± 0.36 mg TE/g DW), but without significant difference compared to stem. In terms of 50% inhibition concentration of DPPH (IC50), the lowest value was retrieved from 100% acetone stem extract (42.66 ± 4.82 μg/mL), however this value is insignificant (p > 0.05) with the top scoring extract, 100% acetone leaf (45.21±4.91 μg/mL) which are both almost similar to the potent standard antioxidant Trolox (48.22 ± 0.79 μg/mL) with insignificant difference. A correlation study of the extracts demonstrated very strong significant positive correlation between phenolic content (TPC) and antioxidant potential especially with DPPH (r = 0.928) and followed by FRAP (r = 0.901). Crude extracts of H. parasitica was found to be highly cytotoxic or antiproliferative to Michigan Cancer Foundation-7 breast cancer cells (MCF-7) when tested for MTT IC50 particularly with selected 100% acetone stem extract at 97.47 ± 2.87 μg/mL, while 5- fluorouracil used as positive standard revealed an IC50 of 3.31 ± 0.15 μg/mL. Interestingly, all the 3 tested extracts (100% acetone, leaf; 100% acetone, stem and 100% methanol, leaf) had no cytotoxic effect up to the maximum extract concentration tested on normal dermal fibroblast cells (IC50 > 500 μg/mL). Current study suggested that extraction solvents and plant parts (for Objective 1 and 3) played significant effect on extractability which depends to the preference of the research, either in terms of targeting maximal extract yield or active phytocompounds. This study proposed the presence of water with intermediate polar solvent (70% acetone) and leaf part could provide increased extraction yield while 100% acetone is suitable for bioactive compound recovery. Not forgotten, H. parasitica also revealed to be a potent source exhibiting anticancer activities but further research need to be done to purify and characterize the extract to identify the potent polar therapeutic compound or candidate against breast cancer. Meanwhile, this report is the first in describing total phenols, flavonoids content, extended assessment of antioxidant activity and anticancer property against breast cancer cell line from extracts of H. parasitica especially on species from Malaysia which may account for some of the medical claims attributed to this plant. Hence, this research and outcome may become a follow up from previous discontinued studies on the exploration of this potent source and lead for new nutraceutical and pharmaceutical approach.